Inclusion of emulsifier in the nutrition of piglets during the maternity phase - Silveira, Érica Caroline; Medeiros, Silvana Lúcia dos Santos; Simão, Sérgio Domingos; Valentim , Jean Kaique; Almeida, Alexander Alexandre de (Revista de Ciências Agroveterinárias, 2024)
The study aimed to evaluate the impact of adding soy lecithin to piglet feed during the maternity phase and its influence on productive performance. Six litters with an average of 12 piglets each (72 piglets) from two distinct lines of sows, Agroceres and DanBred (DB), were used. Different numbers of parities were considered, with DB line animals in their fifth parity and Agroceres line animals in their second and third parities. The sows were selected according to the expected farrowing date to evaluate the use of emulsifier in the pre-starter I diet of piglets. Analysis of variance was performed using feed consumption as a covariate under a completely randomized design (CRD) in a split-plot scheme with two treatments (with and without lecithin) over 21 days of evaluation. Average daily feed intake, daily weight gain, and feed conversion were evaluated. Two treatments were tested with three repetitions, using all piglets from one litter in each repetition. The treatments consisted of a control diet (0% soy lecithin) and a diet with the inclusion of 0.2% soy lecithin. The results of this study indicate that the inclusion of soy lecithin in the pre-starter diet of piglets did not have a significant impact on average feed intake, daily weight gain, feed conversion, or mortality of the animals during the maternity phase. Under the presented experimental conditions, the use of soy lecithin in piglet nutrition during the maternity phase did not demonstrate the ability to alter litter performance.